Age-related deficit in a bimanual joint position matching task is amplitude dependent - Boisgontier, Matthieu P.; Swinnen, Stephan P. (Frontiers in Aging Neuroscience, 2015)
The cognitive load associated with joint position sense increases with age but does not necessarily result in impaired performance in a joint position matching task. It is still unclear which factors interact with age to predict matching performance. To test whether movement amplitude and direction are part of such predictors, young and older adults performed a bimanual wrist joint position matching task. Results revealed an age-related deficit when the target limb was positioned far from (25 deg, p = 0.049) the neutral position, but not when close to (15 deg, p = 0.692; 5 deg, p > 0.999) the neutral joint position, irrespective of the direction (p = 0.693). These results suggest that the difficulty associated with the comparison of two musculoskeletal states increases towards extreme joint amplitude and that older adults are more vulnerable to this increased difficulty.